2021
DOI: 10.3201/eid2702.203767
|View full text |Cite
|
Sign up to set email alerts
|

Early Transmission Dynamics, Spread, and Genomic Characterization of SARS-CoV-2 in Panama

Abstract: We report an epidemiologic analysis of 4,210 cases of infection with severe acute respiratory syndrome coronavirus 2 and genetic analysis of 313 new near-complete virus genomes in Panama during March 9–April 16, 2020. Although containment measures reduced R 0 and R t , they did not interrupt virus spread in the country.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 15 publications
1
21
1
Order By: Relevance
“…Furthermore, this suggests that untracked SARS-CoV-2 community transmission occurred prior to the first confirmed case (April 7, 2020) (Fig 3). Such transmission dynamics has been reported in other countries like the US (e.g., Washington State [20], California [21]) and Panama [26] where viral circulation was reported weeks prior to the first confirmed cases. Interestingly, all isolates in this study encode the D614G spike variant which has been associated with higher viral loads and increased infectivity and transmissibility [46,55].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 65%
See 1 more Smart Citation
“…Furthermore, this suggests that untracked SARS-CoV-2 community transmission occurred prior to the first confirmed case (April 7, 2020) (Fig 3). Such transmission dynamics has been reported in other countries like the US (e.g., Washington State [20], California [21]) and Panama [26] where viral circulation was reported weeks prior to the first confirmed cases. Interestingly, all isolates in this study encode the D614G spike variant which has been associated with higher viral loads and increased infectivity and transmissibility [46,55].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 65%
“…Genomic epidemiology studies have enabled not only the characterization and spread of the VOCs and other viral lineages, but also has been widely implemented to decipher regional transmission dynamics [18], introduction events, and the high-resolution reconstruction of transmission patterns of SARS-CoV-2 in several countries, including China [19], the US (Washington [20], California [21], New York [22]), Chile [23], Colombia [24], Brazil [25], Panama [26], among others.…”
Section: Introductionmentioning
confidence: 99%
“…Whole genome sequencing showed that both viruses belong to two endemic lineages ( Figure 1 B, Supplementary Figure 1): GMI-PA376271 (EPI_ISL_1001457) being A.2.4, previously named A.2.1. ( Franco et al, 2020 ). The second genome GMI-PA584303 accumulated 33 nucleotide (nt) mutations compared with reference MN908947.3 and 23 (21 nt substitutions, 1 deletion, 1 insertion) compared to first sample GMI-PA376271 ( Figure 1 C, Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…SARS-CoV-2 genome analysis showed that both infections were induced by viruses from Panamanian endemic lineages, A.2.4 ( Franco et al, 2020 ) for the first, and A.2.5., containing Spike mutations D614 G and L452R, for the second. Most of the fifthteen induced a.a. changes in the second virus, like the ones in ORF1a, have not been previously described.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth noting that B.1.214.2 displays a large deletion (10 codons) in the N-terminal region of ORF3a, which is not found in other relevant SARS-CoV-2 lineages (Figure 3). Context for the emergence of A.2.5 A.2.5 stems from A.2.4, the dominant lineage in the Panama pandemics during the first half of 2020 [46]. This lineage started spreading very early in the region, with the first detections in oropharyngeal swabs sampled in late February 2020.…”
Section: Resultsmentioning
confidence: 99%